A Case Study of Development of Socialisation through Social Constructivist Approach of Learning A Vital Concern to Teacher Education - Behera, Biswajit (JOURNAL OF INDIAN EDUCATION, 2016)
A qualitative case study was carried out to investigate the social constructivist components of socialisation through small group learning of teacher trainees. What are the ways and how sharing with the social community takes place were understood during the learning situation through focused exploration using Focus Group and Field Note. A total of 15 components were analysed to infer how the teacher trainees learnt to socialise.